Pemberdayaan Siswa Siswi SDN 1 Kebumen Dalam Penguatan Program P5 - Ismiasih, Ismiasih; Arifia Safitri, Amanda; Ismawatul Fitria, Hananda; Lafifatul Muamanah, Irma; Unggul Satria Trengginas, Januarius; Sya’bania Putri, Shasi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
SDN 1 Kebumen is currently implementing the P5 program (Proyek Penguatan Profil Pelajar Pancasila) which is a government program as part of the implementation of the independent curriculum. The empowerment carried out regarding vegetable cultivation and utilization of used goods is motivated by the school's goal of creating a healthy, clean, shady and beautiful school environment as an effort to preserve and manage the environment and develop students to be more productive. The empowerment is carried out through several stages, namely location surveys, delivery of materials, practice and also evaluation. This empowerment activity uses the FGD (Focus Group Discussion) method and also practice. From the results of the evaluation that were asked directly to the training participants, a good response was obtained regarding the empowerment activities carried out. Proven by a percentage result of 100%.